A Novel Schiff Base Complex of Cobalt(II) Self-assembled Synthesis and Magnetic Property - Bi, Jian-Hong; Wang, Hong-Liang; Tao, Wen-Bo; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A new cobalt(II) complex with the molecular formula [CoL]4(ClO4)8-(H2O)8(CH3OH)0.5 {L= (6Z,15Z)-N1',N2'-bis[amino(pyridin-2-yl)methylene]oxalohydrazide} has been synthesized by self-assembly and characterized by elemental analysis, IR spectra and TG measurement. The study of magnetic properties indicates that there is a weak antiferromagnetic interactions between the Co(II) ions in molecule of the complex.